50 Discrimination and characterization of calcium crystal types with a multi-energy spectral photon-counting CT for crystal-related arthropaties: Initial experience and diagnostic performance in vitro. (December 2018) - Viry, A.; Raja, A.Y.; Kirkbride, T.E.; Anderson, N.G.; Combes, C.; Verdun, F.R.; Becce, F.
Abstract : Introduction: Crystal-related arthropathies are a growing global health problem and imaging plays an important role in the diagnosis. Indeed, distinguishing crystal type, whether monosodium urate or one of the calcium crystal types is a clinical challenge because diagnosis and treatment depends on the crystal type involved. Although clinical imaging has made substantial progress in recent years, particularly with the development of dual-energy CT (DECT) protocols in people with longstanding and/or tophaceous gout, the diagnostic performance of DECT remains limited in the early stages of gout 4 . Moreover, while DECT is relatively accurate in distinguishing monosodium urate (MSU) from the various calcium deposits, there is currently no imaging technique capable of noninvasively differentiating one calcium crystal type from another in crystal-related arthropathies, whether in or around the joints. We aimed to determine the in vitro diagnostic performance of multi-energy spectral photon-counting CT (SPCCT) in crystal-related arthropathies. Methods: Four crystal types (monosodium urate, MSU; calcium pyrophosphate, CPP; octacalcium phosphate, OCP; and calcium hydroxyapatite, CHA) were synthesized and blended with agar at the following concentrations: 240, 88, 46, and 72 mg/mL, respectively. Crystal suspensions were scanned on a pre-clinical SPCCT system at 80 kVp using the following four energy thresholds: 20, 30, 40, and 50 keV. Differences in linear attenuation coefficients between the various crystal suspensions were compared using the receiver operating characteristic (ROC) paradigm. Areas under the ROC curves (AUC), sensitivities, specificities, and diagnostic accuracies were calculated. Crystal differentiation was considered successful if AUC > 0.95. Results: Multi-energy SPCCT can accurately differentiate MSU from CPP and CHA, CPP from OCP, and OCP from CHA in vitro. The distinction between MSU and OCP, and CPP and CHA is more challenging. Conclusions: Multi-energy SPCCT can accurately differentiate MSU from CPP and CHA, CPP from OCP, and OCP from CHA in vitro. The distinction between MSU and OCP, and CPP and CHA is more challenging. The accurate identification and characterization of MSU and various calcium crystals would help improve both diagnosis and management of crystal-related arthropathies.